Comparison of the learning achievements of students living in villages and cities during the Covid-19 pandemic - Leila Nur Aisah; Nurahmad Muharram; Wing Prasetya Kurniawan; Budiman Agung Pratama (Universitas Sriwijaya, 2022)
This research was conducted to find out the results of elementary school students' learning achievement after doing online learning. In this study, the researcher used a quantitative descriptive approach with a random sampling of subjects to elementary school students domiciled in Puncu Village and Kediri City, which consisted of 6 schools and 142 students as respondents. Data collection techniques using a questionnaire method. In this study, hypothesis testing uses a t-test. The conclusion from the results of this study is that it is found that there is a comparison of learning achievement of elementary school students who live in cities and in villages have differences in learning achievement after online learning is held. The achievement of students who live in villages has a percentage of 35.92% while the learning achievement of students who live in cities has a percentage of 64.08%. Teachers are expected to continue to provide learning materials for Physical Education, Sports, and Health or PJOK to students in accordance with the core competencies and basic competencies that have been determined so that students remain active, capable and stay healthy while at home.